Headache in Idiopathic Intracranial Hypertension: Findings from the Idiopathic Intracranial Hypertension Treatment Trial - Quiros, Peter (Headache, 2017)
OBJECTIVE: To characterize the phenotype, headache-related disability, medical co-morbidities, use of symptomatic headache medications, and headache response to study interventions in the Idiopathic Intracranial Hypertension Treatment Trial (IIHTT). METHODS: Patients with untreated IIH and mild vision loss enrolled in the IIHTT and randomized to acetazolamide (ACZ) and weight loss or placebo (PLB) and weight loss had prospective assessment of headache disability using the Headache Impact Test 6 (HIT-6) questionnaire. Subjects with headache at the baseline visit were assigned a headache phenotype using the International Classification for Headache Disorders version 3 beta (ICHD-3b). Medication overuse was determined using the participants’ reported medication use for the preceding month and ICHD-3b thresholds for diagnosing medication overuse headache. We investigated relationships between headache disability and various other clinical characteristics at baseline and at six months. RESULTS: Headache was present in 139 (84%) of the 165 enrollees at baseline. The most common headache phenotypes were migraine (52%), tension type headache (22%), probable migraine (16%), and probable tension type headache (4%). Fifty-one (37%) participants overused symptomatic medications at baseline, most frequently simple analgesics. A similar amount of improvement in the adjusted mean (± standard error) HIT-6 score occurred in the ACZ (−9.56 ± 1.05) and PLB groups (−9.11 ± 1.14) at six months (group difference −0.45, 95% CI −3.50 to 2.60, p=0.77). Headache disability did not correlate with any of the studies headache parameters, which included: the lumbar puncture opening pressure at baseline or at six months, body mass index, the amount of weight lost, papilledema grade, perimetric mean deviation, or the use of hormonal contraception. Headache disability was significantly associated with patient-reported quality of life in the physical, mental, and visual domains. CONCLUSIONS: Headache was common, of varied character, disabling, and associated with poorer quality of life in our cohort of patients with mild visual impairment. The lack of correlation between headache disability and cerebrospinal fluid (CSF) pressure at baseline and at the end of the randomized phase of the study implies that headache in IIH may be related to factors other than intracranial hypertension, and that specific headache treatment is needed in addition to therapies directed at lowering CSF pressure.